2022
DOI: 10.1055/s-0042-1756178
|View full text |Cite
|
Sign up to set email alerts
|

Acute Massive and Submassive Pulmonary Embolism: Historical Considerations/Surgical Techniques of Pulmonary Embolectomy/Novel Applications in Donor Lungs with Pulmonary Emboli

Abstract: Pulmonary embolectomy has a chequered history but the quest to surgically treat a patient diagnosed with pulmonary embolism effectively spurred the development of cardiopulmonary bypass and a new dawn for cardiac surgery. The advent of cardiopulmonary bypass, extracorporeal membrane oxygenation, and computed tomography pulmonary angiogram has allowed rapid diagnosis and made surgical pulmonary embolectomy a relatively safe procedure that should be considered when indicated. Pulmonary emboli in donor lungs, oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
(166 reference statements)
0
3
0
Order By: Relevance
“…Ex vivo lung perfusion (EVLP) is an increasingly used method that has been shown to improve substantially the use of rejected lungs with comparable outcomes to normal donor lungs. 34,35 EVLP involves the circulation of an acellular perfusate alongside mechanical ventilation to allow normothermic lung assessment-this allows evaluation, repair, and recognition of marginal donors to expand the donor pool. Brown et al reported a case where EVLP was successfully utilized in donor lungs known to have acute massive PE, with an impressive improvement in P/F ratio from 268 to 425.…”
Section: Managementmentioning
confidence: 99%
“…Ex vivo lung perfusion (EVLP) is an increasingly used method that has been shown to improve substantially the use of rejected lungs with comparable outcomes to normal donor lungs. 34,35 EVLP involves the circulation of an acellular perfusate alongside mechanical ventilation to allow normothermic lung assessment-this allows evaluation, repair, and recognition of marginal donors to expand the donor pool. Brown et al reported a case where EVLP was successfully utilized in donor lungs known to have acute massive PE, with an impressive improvement in P/F ratio from 268 to 425.…”
Section: Managementmentioning
confidence: 99%
“…1 In searching for strategies that may make a dent on this dismal mortality rate, investigators have, in the last decade, shown renewed interest in the potential beneficial role of venoarterial (V-A) extracorporeal membrane oxygenation (ECMO) in the treatment of patients with high-risk PE and, in particular, those with circulatory collapse or cardiac arrest. [2][3][4][5][6][7][8][9][10][11] In this review, we outline the mechanism, design, and operation of the V-A ECMO system; provide a brief overview of the historical background of this treatment modality; and discuss current and future applications.…”
mentioning
confidence: 99%
“…1 In searching for strategies that may make a dent on this dismal mortality rate, investigators have, in the last decade, shown renewed interest in the potential beneficial role of venoarterial (V-A) extracorporeal membrane oxygenation (ECMO) in the treatment of patients with high-risk PE and, in particular, those with circulatory collapse or cardiac arrest. 2 3 4 5 6 7 8 9 10 11…”
mentioning
confidence: 99%